Athleticism in NCAA D-III: It Ain't Only Football That Matters. (October 2019) - Segura, Jerome; Willner, Jonathan
Most D-III universities field a football team, yet little is known about how a football program can influence the quality of the student body or rate at which students graduate. To evaluate these advertising and effectiveness effects of football, we build balanced panel data sets using available private D-III universities (80–90% of all D-III universities) from 2003 through 2010. We also account for overall athletic participation. Using generalized linear model (GLM) and linear-in-means estimation procedures, we find conditional evidence of the advertising and effectiveness hypotheses of football. We find that female athletes are successful as advertising and effectiveness, while male athletes are negative advertising and of neutral to negative effectiveness.